Modeling an Alternative Expression of Covered Interest Parity – in Inflation Targeting Economies of Emerging Asia - Ramanathan, Suresh; Kwek, Kian-Teng (Journal of Reviews on Global Economics, 2014)
We establish an alternative form of expressing the covered interest parity model that incorporates the onshore and offshore foreign exchange forward market of inflation targeting economies of Emerging Asia, which provides the ability to identify if there is the occurrence of covered interest parity in foreign exchange forward markets.